Relationship between form 4 students perceptions of science classroom environment with attitudes towards science - Leona A Candia (2017)
Science educators have been interested in understanding students' achievement and have undergone decades of studies about it. It is essential to develop positive attitudes towards science as one of the legitimate goals of science education in Malaysia. The purpose of this study was to investigate the relationship between students' perceptions of science classroom environment and their attitudes towards science. This study was a non-experimental quantitative research and employed a sample survey method to collect data. Samples were selected by using the two-stage cluster random sampling. In this study, the Test of Science-Related Attitudes (TOSRA) was adopted to measure students' attitudes towards science while students' perception towards classroom environment was measured with 'What Is Happening In This Class' (WIHIC) instrument. The seven subscales in TOSRA measured were Social Implications of Science, Normality of Scientists, Attitude to Scientific Inquiry, Adoption of Science Lessons, Leisure Interest in Science, and Career Interest in Science. The seven subscales in WIHIC measured were Student Cohesiveness, Teacher Support, Involvement, Investigation, Task Orientation, Cooperation, and Equity. Independent sample t-test, Pearson Product Moment Correlation and Multiple Regression Analysis were used to test the stated null hypotheses at a predetermined significance level, alpha = .05. Data analysis showed that both gender and school locations do not have a significant effect on students' perceptions of science classroom environment. Apart from that, gender also did not have a significant effect on students' attitudes towards science. However, school locations had a significant effect on students' attitudes towards science in which urban schools' students are shown to display more positive attitudes towards science than their rural peers. Correlation analysis results showed that there was positive low to moderate significant correlations between students' perceptions of science classroom environment and their attitudes towards science. Multiple regression analysis showed that students' perception of science classroom environment is a significant predictor of students' attitudes towards science in Tenom and Kata Kinabalu. Further analysis showed that WIHIC's subscale of Task Orientation is the most significant predictor to students' attitudes towards science.